The effectiveness of Balint group work on the quality of work life, resilience, and nurse–patient communication skills among psychiatric nurses: a randomized controlled trial - Yousefzadeh, Negar Kiani; Dehkordi, Mansoureh Kiani; Vahedi, Mohsen; Astaneh, Ali Nazeri; Bateni, Fatemeh Sadat (Frontiers in Psychology, 2024)
Background: Balint group training has gained popularity in medical practices as an intervention designed to enhance the quality of life, well-being, and communication skills of healthcare practitioners. Psychiatric nurses, in particular, encounter distinct challenges and stressors inherent in their profession, necessitating the development and implementation of effective interventions to assist them in coping with the difficulties they experience. In this vein, the current study aimed to investigate the effectiveness of Balint group training on quality of work life, resilience, and nurse-patient communication skills among psychiatric nurses. Methods: Thirty psychiatric nurses from Razi Hospital in Tehran were recruited via the purposeful sampling method in 2022 and were randomly assigned to either the Balint group, consisting of eight weekly one-hour training sessions, or a control group. Participants completed the Walton Quality of Work Life Questionnaire, Connor-Davidson Resilience Scale, and Communication Skills Scale before and after the intervention. The data were analyzed using the Analysis of Covariance (ANCOVA).The study found no significant differences between the Balint group and the control group in terms of quality of work life, resilience, and nurse-patient communication skills. Conclusion: Findings suggest that Balint group training was not an effective intervention for improving the well-being and communication skills of psychiatric nurses. However, the study highlights the need for further investigation into the potential factors that may explain the lack of significant gains and offers insights for future research in this area.